Multiplexing 200 spatial modes with a single hologram. (5th October 2017) - Rosales-Guzmán, Carmelo; Bhebhe, Nkosiphile; Mahonisi, Nyiku; Forbes, Andrew
Abstract: The on-demand tailoring of light's spatial shape is of great relevance in a wide variety of research areas. Computer-controlled devices, such as spatial light modulators (SLMs) or digital micromirror devices, offer a very accurate, flexible and fast holographic means to this end. Remarkably, digital holography affords the simultaneous generation of multiple beams (multiplexing), a tool with numerous applications in many fields. Here, we provide a self-contained tutorial on light beam multiplexing. Through the use of several examples, the readers will be guided step by step in the process of light beam shaping and multiplexing. Additionally, we provide a quantitative analysis on the multiplexing capabilities of SLMs to assess the maximum number of beams that can be multiplexed on a single SLM, showing approximately 200 modes on a single hologram.